2010
DOI: 10.1186/1471-213x-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chick (Gallus gallus) middle ear columella formation

Abstract: BackgroundThe chick middle ear bone, the columella, provides an accessible model in which to study the tissue and molecular interactions necessary for induction and patterning of the columella, as well as associated multiple aspects of endochondral ossification. These include mesenchymal condensation, chondrogenesis, ossification of the medial footplate and shaft, and joint formation between the persistent cartilage of the extracolumella and ossified columella. Middle and external ear defects are responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…Study of osteogenesis of periosteum cells in the columella has shown two initiation sites, an initial one in the shaft (main body) of the columella and then a second site at the base of the footplate (Wood et al, 2010). The relatively late differentiation of the footplate base in the chick is similar to our studies in the mouse, which have shown that the mesodermal part of the footplate develops later than the neural crest part.…”
Section: Stapedial Footplate and Otic Capsule Form Togethersupporting
confidence: 83%
“…Study of osteogenesis of periosteum cells in the columella has shown two initiation sites, an initial one in the shaft (main body) of the columella and then a second site at the base of the footplate (Wood et al, 2010). The relatively late differentiation of the footplate base in the chick is similar to our studies in the mouse, which have shown that the mesodermal part of the footplate develops later than the neural crest part.…”
Section: Stapedial Footplate and Otic Capsule Form Togethersupporting
confidence: 83%
“…Immunostaining was carried out using our standard protocol [34]. Briefly, sections were blocked in PBS with 0.1% TritonX-100 and 0.2% bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%
“…Ossification begins in the shaft at the proximal end, then in the footplate, and proceeds up the shaft toward the distal extracolumella, forming the joint region with the cartilaginous extracolumella (2, 25–27). …”
Section: Morphologymentioning
confidence: 99%
“…The function of the middle ear is to transmit and amplify sound from the external environment, across the middle ear cavity, to the inner ear (1, 2). The middle ear is a composite organ, produced from all three germ layers, and the neural crest contributing to its development (3–7).…”
Section: Introductionmentioning
confidence: 99%